Changes in the level of technical-tactical readiness indicators of tennis players at the stage of preliminary basic training - Shevchenko, O. (Slobozhanskyi herald of science and sport, 2018)
Purpose: investigate changes in the level of technical-tactical readiness indicators of tennis players at the stage of preliminary basic preparation of the preparatory period of the macrocycle.